Risk factors of breast cancer recurrence in pathologic complete response achieved by patients following neoadjuvant chemotherapy: a single-center retrospective study - Choi, Joon Young; Woen, Doyoun; Jang, Sung Yoon; Lee, Hyunjun; Shin, Dong Seung; Kwak, Youngji; Lee, Hyunwoo; Chae, Byung Joo; Yu, Jonghan; Lee, Jeong Eon; Kim, Seok Won; Nam, Seok Jin; et al. (Frontiers in Oncology, 2023)
Objective Pathologic complete response (pCR) of breast cancer after neoadjuvant chemotherapy (NAC) is highly related to molecular subtypes. Patients who achieved tumor pCR after NAC have a better prognosis. However, despite of better prognosis, pCR patients have a potential for recurrence. There is little evidence of risk factors of recurrence in patients with pCR. We aim to analyze factors associated with tumor recurrence in patients who achieved pCR. Methods This study retrospectively reviewed the data of patients diagnosed with breast cancer who achieved pCR after receiving NAC between January 2009 and December 2018 in Samsung Medical Center. pCR was defined as no residual invasive cancer in the breast and axillary nodes even if there is residual ductal carcinoma in situ (ypT0 or ypTis with ypN0). Breast cancers are classified into 4 subtypes based on hormone receptors (HR) and human epithelial growth factor receptor 2 (HER2) status. Patients who had bilateral breast cancer, ipsilateral supraclavicular or internal mammary lymph node metastasis, inflammatory breast cancer, distant metastasis, unknown subtype, and histologically unique case were excluded from the study. Results In total 483 patients were included in this study except for patients who corresponded to the exclusion criteria. The median follow-up duration was 59.0 months (range, 0.5-153.3 months). Breast cancer recurred in 4.1% of patients (20 of 483). There was a significant difference in clinical T (P = 0.004) and clinical N (P = 0.034) stage in the Kaplan-Meier curve for disease-free survival. Molecular subtypes (P = 0.573), Ki67 (P = 1.000), and breast surgery type (P = 0.574) were not associated with tumor recurrence in patients who achieved pCR after NAC. In the clinical T stage and clinical N stage, there was a significant difference between recurrence and no-recurrence groups (clinical T stage; P = 0.045, clinical N stage; P = 0.002). Univariable Cox regression revealed statistical significance in the clinical T stage (P = 0.049) and clinical N stage (P = 0.010), while multivariable Cox regression demonstrated non-significance in the clinical T stage (P = 0.320) and clinical N stage (P = 0.073). Conclusion Results in this study showed that clinical T, clinical N stage, and molecular subtypes were not statistically significant predictors of recurrence in patients who achieved pCR after NAC. In spite of that, pCR after NAC may be more important than clinical staging and molecular subtype in early breast cancer. In addition, escalated treatments for patients with HER2 + or triple-negative tumors would be considered with a strict patient selection strategy to prevent over-treatment as well as achieve pCR.